Recommendations for repositories and scientific gateways from a neuroscience perspective - Sandström, Malin; Abrams, Mathew; Bjaalie, Jan G.; Hicks, Mona; Kennedy, David N.; Kumar, Arvind; Poline, Jean-Baptiste; Roy, Prasun K.; Tiesinga, Paul; Wachtler, Thomas; Goscinski, Wojtek J. (Nature Research, 2022)
Digital services such as repositories and science gateways have become key resources for the neuroscience community, but users often have a hard time orienting themselves in the service landscape to fnd the best ft for their particular needs. INCF has developed a set of recommendations and associated criteria for choosing or setting up and running a repository or scientifc gateway, intended for the neuroscience community, with a FAIR neuroscience perspective.
This paper is submitted by the author of IIT (BHU), Varanasi
Keywords: scientific gateways; neuroscience